DOES STUNTING ASSOCIATE TO THE TOTAL FACTOR PRODUCTIVITY? A CASE OF EAST JAVA, INDONESIA - Mohammad Zeqi Yasin; Hesti Retno Budi Arini (East Java Economic Journal, 2019)
Although stunting prevalence and many economic indicators are claimed associating to long-term correlation, the finding of this question might signal the policy arrangement that should be taken. This study aims to examine the correlation of Total Factor Productivity (TFP) growth and stunting prevalence of the 38 districts in East Java, Indonesia from 2017 to 2019. By employing fixed-effect model to estimate TFP growth using Growth Accounting approach, as well as quantitative approach and pairwise correlation, to identify the correlation between TFP growth and stunting prevalence, this study found that there is a negative association between TFP growth and stunting prevalence. Moreover, an intriguing finding reveals that districts with largest Gross Domestic Regional Product (GDRP) shows the strongest correlation amongst others. A plausible reason of this result is that district with large GDRP might allocate more budget for stunting reduction programs, for example the district of Sidoarjo. The negative association between TFP growth and stunting prevalence is then confirmed by statistical results of pairwise correlation from Pearson and Spearman’s Rho that both show significant correlation between those two indicators by larger than 0.3, indicating a non-trivial association between TFP growth and stunting prevalence. Keywords: Stunting Prevalence, TFP Growth, East Java.JEL : I15, I18, O47